Estilos geotectónicos bidimensionales y tridimensionales interbloques: Una nueva categoría neotectónica para la determinación de morfoestructuras montañosas - José Ramón Hernández Santana; Mario Arturo Ortiz Pérez; Antonio R. Magaz García (Investigaciones Geográficas, 1994)
Cuban Archipelago geologic evolution reveals a W to E migration in Early Mezo–Cenozoic vulcanism and magmatism as well as an increased activity in neotectonics, seismicity, and recent secular endodynamics originating a conspicuous geomorphological variety in the eastern edge in which, along the tectogenetical axis occupied by the Barlett deeptrench, horizontal left–lateral displacements occur. During the relief developmental neotectonic–geomorphologic stage, the convergent compressive movements were discontinued existing a horst–and–graben–like block tectonical expansion regime with peculiar styles for every mountainous macro and mesomorphoestructures. Among the 18 different tridimensional interblock interrelation system shaping the Eastern Cuba mountains there are: arch isometric–block; stepped asymmetral–jibbed block; alternate asymmetral horst–and–graben–blocks; stepped block isometric; arch–horst linear, jibbed; horst–and–graben blocks alternate symetric with transitional–transversal asymmetral stepping; irregularly stepped–jibbed blocks; block linear; arch–horst linear; block irregular; monolitic isometric; stepped–horst irregular; stepped–horst linear; stepped, jibbed and bearing–rotated horst linear; irregular block isometric; horst– and–graben block with strong inner fracture stepped alternate; and asymmetral horst–and–graben alternate. At the same time, in this paper we report some mexican geotectonic models: the flower structure of volcanic complex of Temascalcingo, Acambay´s graben; the continental rifting in the Amatlán de Cañas Volcanic field; and the branching scheme of the Sierra Atravesada–Istmo de Tehuantepec.